SOCIALIZATION AND TRAINING OF BATIK PRODUCTION FOR BUMDES SUWALUH BALONGBENDO VILLAGE, SIDOARJO - Andrian Firdaus Yusuf al Qordhowi (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
Batik production has strategic potential to support rural economic development and cultural sustainability; however, many village-owned enterprises (BUMDes) face persistent challenges related to production efficiency, managerial capacity, and institutional sustainability. This community service aimed to strengthen batik production performance and organizational capacity of BUMDes Suwaluh in Balongbendo Village, Sidoarjo, through an integrated socialization and training program. The service employed a Participatory Action Research (PAR) approach, emphasizing collective problem diagnosis, participatory training, action, reflection, and evaluation. Data were generated through observation, interviews, questionnaires, and production records, and were analyzed using descriptive, comparative, and correlational techniques to assess changes in technical, economic, and organizational indicators. The results demonstrate that the PAR-based intervention improved production quality consistency, enhanced cost awareness and basic financial management skills, and fostered stronger collective coordination within the batik unit. Importantly, the findings indicate that these outcomes emerged not merely from skill transfer, but from participatory learning processes that enabled artisans to internalize standards and jointly manage production decisions. In conclusion, this community service confirms that participatory approaches are critical for translating cultural-based training into sustainable economic and institutional gains. Scientifically, the program contributes an evidence-based model of PAR-driven community empowerment, addressing gaps in prior batik-focused community service studies that lacked analytical evaluation of impact pathways.